Dielectric relaxations in PVDF/BaTiO3 nanocomposites - Chanmal, Chetan; Jog, Jyoti Prakash (Express Polymer Letters, 2008)
The present work aims at the study of molecular relaxations in PVDF/BaTiO3 nanocomposites using broadband dielectric spectroscopy. The nanocomposites of PVDF with BaTiO3 ( 10-30% by wt%) are prepared using simple melt mixing method. In dielectric permittivity study, two relaxation processes are identified corresponding to the crystalline, glass transition in the PVDF/BaTiO3 nanocomposites. The peaks shift to higher frequencies as the temperature is increased. Electric modulus formalism is used to analyze the dielectric relaxations to overcome the conductivity effects at low frequencies. In M `' spectra two peaks are observed only at high temperature and low frequency whereas a single relaxation peak appears at low temperatures. The single relaxation peak appearing at low temperatures is the alpha(c) relaxation attributed to crystalline chain relaxation in PVDF and the second relaxation peak which appears only at high temperatures and at a frequency lower than alpha(c) relaxation is identified as MWS relaxation. The temperature dependence of alpha(c) relaxation and MWS relaxation follows Arrhenius type behavior.
Keywords: dielectric spectroscopy; Interfacial polarization; MWS relaxation; Nanocomposites

Study of dielectric behavior in PVDF/clay nanocomposites - Chanmal, Chetan; Jog, Jyoti Prakash (E-Polymers, 2009)
A high dielectric permittivity nanocomposite based on poly( vinylidene fluoride) (PVDF) and organically modified clay is reported. The present work aims to study the effect of clay on dielectric behavior of PVDF. The dielectric permittivity study shows a remarkable enhancement in the permittivity of nanocomposites in the low frequency region. The obtained permittivity values fits quite well to the prediction of dielectric permittivity from Vo-Shi model, which takes contribution of interface to permittivity into account. This enhanced permittivity in nanocomposites is attributed to the presence of interfacial polarization. The interface effect is further studied with cole-cole plot analysis. The dielectric loss study of pristine PVDF shows two relaxations associated with segmental (glass transition relaxation) and crystalline chain relaxation. However in the PVDF/Clay nanocomposites crystalline relaxation peak disappears which is attributed to the formation of the beta phase in PVDF/clay nanocomposites.

Enhanced dielectric permittivity in poly (vinylidene) fluoride/multiwalled carbon nanotubes nanocomposite thin films fabricated by pulsed laser deposition - Chanmal, Chetan; Deo, Meenal S.; Jog, Jyoti Prakash (Applied Surface Science, 2011)
The fabrication of high quality thin films of poly (vinylidene fluoride) embedded with multiwalled carbon nanotubes using pulsed laser deposition technique is reported. The prepared films were characterized for structural, morphology and dielectric properties. The morphology analysis revealed uniform dispersion of multiwalled carbon nanotubes throughout the polymer matrix. X-ray diffraction results suggested that the poly (vinylidene fluoride) film is in amorphous phase while addition of multiwalled carbon nanotubes showed presence of crystalline peaks in the nanocomposites films. It was interesting to note that the nanocomposite films exhibits significant enhancement of the ferroelectric beta-phase as evidenced by the X-ray diffraction and Fourier transform infrared spectroscopy results. The dielectric analysis shows a remarkable enhancement in the dielectric permittivity of nanocomposites with lower loss and conductivity level. The results can be attributed to the formation of minicapacitor network and relatively higher percolation threshold in the nanocomposites. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Dielectric permittivity; Ferroelectric polymer; Percolation threshold; pulsed laser deposition; Thin films

Strong electric field modulation of transport in PVDF/MWCNT nanocomposite near the percolation threshold - Chanmal, Chetan; Deo, Meenal S.; Rana, Abhimanyu; Jog, Jyoti Prakash; Ogale, Satishchandra B. (Solid State Communications, 2011)
A nanocomposite comprising of multiwalled carbon nanotubes (MWCNT) embedded in ferroelectric Poly(vinylidene fluoride) PVDF polymer matrix is examined for electric field induced transport modulation. The pulsed laser deposition (PLD) grown thin films of the nanocomposite with different MWCNT content were characterized. When used as a channel layer in a field effect transistor configuration, a strong electric field modulation of the transport was realized just below the percolation threshold. We believe that this nanocomposite non-percolating channel concept can provide several opportunities for FET devices for organic electronics. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Field effect device; pulsed laser deposition; PVDF; Scanning tunneling microscopy